Uteine fibroids (Journal of Universal Science Research, 2023)
Uterine fibroids, also known as leiomyomas, are a prevalent gynecological condition that affects a significant number of women during their reproductive years. These noncancerous growths, arising in the uterus, can lead to a range of symptoms, including heavy menstrual bleeding, pelvic pain, and even fertility issues. This article delves into the multifaceted world of uterine fibroids, exploring their causes, symptoms, and various treatment options. Article also serves as an informative guide, empowering women to navigate the complex landscape of uterine fibroids, make informed decisions, and take proactive steps toward improved reproductive health and overall well-being